CHEMICAL COMPOSITION OF SEAWATER IN NEOPROTEROZOIC: RESULTS OF FLUID INCLUSION STUDY OF HALITE FROM SALT RANGE (PAKISTAN) AND AMADEUS BASIN (AUSTRALIA) - Kovalevych V.M.; Peryt T.M.; Petrychenko O.Y.; Zhukova S.A.; Marshall T. (My University, 2006)
Data on chemical composition of brines in primary inclusions of marine halites and on mineralogy of marine evaporites and carbonates lead to the conclusion that during the Phanerozoic two long-term cycles of chemical composition of seawater existed. During each of those cycles, seawater dominantly a Na-K-Mg-Ca-Cl (Ca-rich) type changed to a Na-K-Mg-Cl-SO 4 (SO4-rich) type. Recrystallised halite from the uppermost Neoproterozoic Salt Range Formation (ca. 545 Ma) in Pakistan, contains solitary inclusions indicating SO4-rich brines. This supports the concept derived from the study on primary fluid inclusions from the Neoproterozoic Ara Formation of Oman; SO4-rich seawater existed during latest Neoproterozoic time (ca. 545 Ma). In contrast, samples of recrystallised halite from the Bitter Springs Formation (840-830 Ma) in Australia contain inclusion brines that are entirely Ca-rich, indicating that basin brines and seawater were Ca-rich during deposition of central Australian evaporites. These combined data supported by the timing of aragonite and calcite seas suggest that during the Proterozoic, significant oscillations of the chemical composition of marine brines, and seawater, occurred, which are similar to those known to exist during the Phanerozoic. It is suggested that Ca-rich seawater dominated for a substantial period of time (more than 200 Ma), at 650 Ma, this was replaced by SO4-rich seawater, finally returning to Ca-rich seawater at 530 Ma. © 2005 Elsevier B.V. All rights reserved.
Keywords: AUSTRALIA; EVAPORITES; FLUID INCLUSIONS; GEOCHEMISTRY; HALITE; NEOPROTEROZOIC; PAKISTAN; Precambrian::Proterozoic::Neoproterozoic; Докембрий::Протерозой::Неопротерозойская